2020
DOI: 10.2478/bjmg-2020-0004
|View full text |Cite
|
Sign up to set email alerts
|

Association of the brain-derived neurotrophic factor Val66Met polymorphism with body mass index, fasting glucose levels and lipid status in adolescents

Abstract: Brain-derived neurotrophic factor (BDNF) has an important role in energy balance. It suppresses food intake, reduces hepatic glucose production and converts white fat into brown fat in adipose tissue, leading to energy dissipation, lowered blood glucose and a lean phenotype. Studies have shown that the single nucleotide polymorphism (SNP) Val66Met within BDNF may be associated with obesity, insulin sensitivity, type 2 diabetes mellitus (T2DM) and dyslipidemia. The objective of the study was to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…Although all participants in our study were living with overweight or obesity, our findings that the BDNF polymorphism could not differentiate carriers of Val vs. Met variants on BMI is consistent with studies that included youth with and without obesity from Spain ( Arija et al, 2010 ), Mexico ( León-Mimila et al, 2013 ) and Serbia ( Vidovic et al, 2020 ). Similarly, Friedel et al (2005) reported that no differences in BDNF allele frequency were observed in German children and youth with severe obesity, underweight students, and normal weight controls.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Although all participants in our study were living with overweight or obesity, our findings that the BDNF polymorphism could not differentiate carriers of Val vs. Met variants on BMI is consistent with studies that included youth with and without obesity from Spain ( Arija et al, 2010 ), Mexico ( León-Mimila et al, 2013 ) and Serbia ( Vidovic et al, 2020 ). Similarly, Friedel et al (2005) reported that no differences in BDNF allele frequency were observed in German children and youth with severe obesity, underweight students, and normal weight controls.…”
Section: Discussionsupporting
confidence: 88%
“…It is noteworthy, however, that the Val66Met polymorphism is highly conserved and the Val66 prodomain BDNF ligand has been shown to reduce dendritic spine density in hippocampal neurons and facilitates long-term hippocampal depression (Guo et al, 2016), an effect that is blunted by the Met prodomain BDNF (Mizui et al, 2016). This highlights that the Met66 prodomain ligand may confer selective advantages to hippocampal structure and plasticity, which may also explain, in part, findings that the Met-allele carriers have exhibited lower cardiometabolic disease risk in children (Kalenda et al, 2018;Vidovic et al, 2020), lower BMI in healthy adults (Sustar et al, 2016), and fewer CVD events and milder CVD severity in adult cardiac patients (Jiang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some authors have suggested the Met-allele carriers have lower risk for obesity, postprandial glucose and HbA1c levels 25 , 44 , 45 . Additionally, also some studies have observed no association with anthropometric indices and lipid profile 46 48 . The inconsistent results have been revealed on the association between the Val66Met polymorphism and obesity and lipid profile, proposing that environmental factors like dietary intake may be modify this association.…”
Section: Discussionmentioning
confidence: 96%